Use and Awareness of Online Public Access Catalogue (OPAC) by Students and Faculty members of Anna University Regional Campus, Coimbatore, Tamil Nadu – A Case Study (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper aims to present the results of a survey conducted to determine the use of online public access catalogue (OPAC) at the library of Anna University Regional Campus, Coimbatore. The questionnaire based survey conducted at the library. 190 samples of the questionnaire is distributed randomly between the staff and students of Anna University Regional Campus, Coimbatore, out of which 154 completed and valid questionnaires (81.00%) are received for analysis. The data received from the respondents through the questionnaires is analyzed. The result of the study reveals that a significant number of users search information regarding the library material through despite encountering problems. It is suggested that the library should organize quality instruction programmes to improve knowledge and skills of the users.